2013
DOI: 10.1002/pbc.24686
|View full text |Cite
|
Sign up to set email alerts
|

Mifamurtide in metastatic and recurrent osteosarcoma: A patient access study with pharmacokinetic, pharmacodynamic, and safety assessments

Abstract: Purpose This non-randomized, patient-access protocol, assessed both safety and efficacy outcomes following liposomal muramyl –tripeptide-phosphatidylethanolamine (L-MTP-PE; mifamurtide) in patients with high-risk, recurrent and/or metastatic osteosarcoma. Methods Patients received mifamurtide 2 mg/m2 intravenously twice-weekly ×12 weeks, then weekly ×24 weeks with and without chemotherapy. Serum concentration-time profiles were collected. Adverse events within 24 hours of drug administration were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 50 publications
4
42
0
Order By: Relevance
“…This agent is currently approved for use in non-metastatic osteosarcoma in Europe, Mexico, South Korea, Switzerland, and Israel. 54 Monoclonal antibody therapy against the OS tumor antigen, GD2, is a new emerging therapy that will be investigated by the Children's Oncology Group. GD2 is a surface glycolipid that is expressed at high levels in osteosarcomas.…”
Section: Osteosarcoma Tumor Genomicsmentioning
confidence: 99%
“…This agent is currently approved for use in non-metastatic osteosarcoma in Europe, Mexico, South Korea, Switzerland, and Israel. 54 Monoclonal antibody therapy against the OS tumor antigen, GD2, is a new emerging therapy that will be investigated by the Children's Oncology Group. GD2 is a surface glycolipid that is expressed at high levels in osteosarcomas.…”
Section: Osteosarcoma Tumor Genomicsmentioning
confidence: 99%
“…Results from the metastatic cohort of INT0133 pointed in the same direction as in non-metastatic patients but were not statistically significant 49 . Come 2016, there is additional evidence that L-MTP-PE has a favorable safety profile: a patient access study of 200 patients reported 3,679 infusion-related adverse events after 7,482 infusions, commonly chills, fever, headache, and fatigue, but only rarely severe 50 . However, there have been no further trials which shed more light upon the potential efficacy of the drug, so uncertainties remain regarding its potential role.…”
Section: Advances In Systemic Treatmentmentioning
confidence: 99%
“…An access study (MTP-OS-403, NCT00631631) (Anderson et al 2014a ) for MTP in patients with relapsed and/or recurrent osteosarcoma was done after initial approval by the European Medical Agency and at the request of the US Food and Drug Administration. This study also helped better defi ne pharmacodynamics, pharmacokinetics, and safety profi le of this drug in osteosarcoma.…”
Section: Mtp-pementioning
confidence: 99%